Studi Biblika Kontekstual Dalam Kehidupan Iman Kristen Di Era Disrupsi - Wandrio Salewa (Program Pascasarjana UKIM, 2022)
This article aims to explore the challenges of contextual biblical studies in the disruptive era. This era is marked by the development of digital technology such as smartphones, so that everyone can easily prepare sermon materials instantly from various interpretation applications on a smartphone, without basing it on in-depth Bible interpretation rules. The author presents the concepts and methods of biblical interpretation as a form of contextual biblical studies to overcome the use of instant sermons from various interpretation applications. By using a qualitative approach and the type of literature and descriptive research. From this research, it is found that contextual biblical studies are a solution to overcome biblical interpretation and the use of sermons that seem appropriate and instant regardless of the context of the text, the context of the interpreter, and the context of the listener. It also gives the impression of belittling or belittling sermon preparation and the rules of biblical interpretation. Contextual biblical studies can be used to avoid mistakes in interpreting and preparing sermons while at the same time producing biblical and contextual interpretations.